The Influence of Organizational Culture, Job Satisfaction, and Work Motivation on Employee Performance at the PMK, PP & PA Office of - Hanif , Yunita (Terbuka Journal of Economics and Business, 2020)
The Dinas PMK (Kelurahan Community Empowerment), PP (Women's Empowerment), and PA (Child Protection) is the implementing element of government affairs which fall under regional authority. This institution is led by a Head of Service who is under and responsible to the Mayor through the Regional Secretary. The PMK, PP, and PA office have the task of assisting the Mayor to carry out government affairs which fall under regional authority and the task of assisting in the empowerment of village communities, empowering women and protecting and fulfilling children's rights. This research is a quantitative research with a descriptive approach. The method used in this study is multiple linear regression analysis with a sample of 41 respondents. The purpose of this study was to analyze the influence of organizational culture, job satisfaction and work motivation directly on employee performance at the PMK, PP & PA Office of Sibolga City. And also, to determine the effect of organizational culture, job satisfaction and work motivation indirectly on the performance of employees in the PMK, PP & PA Office of Sibolga City. The results showed that organizational culture, job satisfaction, and work motivation partially and simultaneously had a positive and significant effect on the performance of the employees of the PMK, PP & PA Office of Sibolga City. It is suggested that the leadership of the PMK, PP & PA Office of Sibolga City pay more attention to indicators of organizational culture, job satisfaction, and work motivation; and systems that have been running well so far to be maintained, evaluated and improved in order to improve employee performance.